2020
DOI: 10.1007/s00779-020-01455-7
|View full text |Cite
|
Sign up to set email alerts
|

A framework to estimate cognitive load using physiological data

Abstract: Cognitive load has been widely studied to help understand human performance. It is desirable to monitor user cognitive load in applications such as automation, robotics, and aerospace to achieve operational safety and to improve user experience. This can allow efficient workload management and can help to avoid or to reduce human error. However, tracking cognitive load in real time with high accuracy remains a challenge. Hence, we propose a framework to detect cognitive load by non-intrusively measuring physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…In [145], blink duration and frequency were also shown to maximize at the lowest speed in the video game, and as the workload increased, blink frequency decreased. In [17] blink rate decreased from low to medium cognitive load but no further change was observed in high cognitive load. Borys et al also showed that maximum blink duration correlated strongly with the number of errors in high cognitive load of an arithmetic task [146].…”
Section: Metrics Related To Cognitive Workloadmentioning
confidence: 74%
See 4 more Smart Citations
“…In [145], blink duration and frequency were also shown to maximize at the lowest speed in the video game, and as the workload increased, blink frequency decreased. In [17] blink rate decreased from low to medium cognitive load but no further change was observed in high cognitive load. Borys et al also showed that maximum blink duration correlated strongly with the number of errors in high cognitive load of an arithmetic task [146].…”
Section: Metrics Related To Cognitive Workloadmentioning
confidence: 74%
“…According to cognitive load theory, there are three types of cognitive load: 1) intrinsic load 2) extraneous load and 3) germane load [16]. The intrinsic load comes from the complexity of the task and its association with the user, extraneous load is caused by the presentation style of the material and germane load refers to the ability of the user to fully understand the material [17].…”
Section: Cognitive Workloadmentioning
confidence: 99%
See 3 more Smart Citations